(untitled) (Fiep Bulletin - online, 2011)
Human aging leads to declines in organ function, reducing the health and quality of life. One of the serious problems that can lead the elderly to disability, poor quality of life and even early death is the rate of falls. Among other factors, such falls occur due to losses that seniors have in their motor coordination and its psychomotor and proprioceptive stimuli. It lies in the method of ’Education Movement "Ivaldo Bertazzo of a set of tools that can act to significantly reduce the incidence of falls in older adults. Thus, the present work through a case study in UNAT / UniFOA, aims to analyze quantitatively the Education Movement is able to improve balance and hence reduce the incidence of falls. The instrument for obtaining quantitative data of the research was the testing protocol of balance "Performance-oriented mobility assetment of gait and balance" (POMA), in an adapted version authored by Shumway-Cook and Woollacott (1995). The results point to the evidence of the effectiveness of the method in the prevention of falls among the elderly.